Digital transformation playground : literature review and framework of concepts - Pihir, Igor (Array, 2019)
Digital transformation (DT) introduces strategy-oriented and customer-centric changes, based on innovative usage of emerging information and communication technology (ICT), to implement improved or new processes in modern organizations. This paper provides insights into academic publishing trends and offers an analysis of scientific fields in which researches were made followed by a brief analysis of the most influential articles. Paper also identifies and discusses key determinants and influence factors of DT and some emerging trends and technologies, in order to explain organizational and technological context of DT. For better understanding of this mix of business and ICT related concepts, a framework of concepts on DT was developed and called Digital transformation playground (DTP). Its purpose is to get better understanding of what are the mainstream concepts of today, what other and emerging ICT or digitalization concepts in the context of DT arise, and how these technology elements impact business related concepts.